Gaia Space Mission - Teixeira, Ramachrisna (Cadernos de Astronomia, 2022)
With careful and systematic observations of the sky, human beings have been building and refining their knowledge about the Universe and about themselves for a long time. The observational magnitudes on which astronomy rests are finally being measured abundantly and with unimaginable precision thanks to the Gaia Space Mission of the European Space Agency. With its three data releases (2016, 2018 and 2020/22), we have, today, in our hands, observational data in quantity and quality that until very recently we did not even dream of. Among them, the most important greatness of all astronomy: the distance of more than 1.5 billion stars that allows us to say where they are, what they look like and how they ’’dance’’, thus starting a new era in the study of the Galaxy and the Universe. Universe. This data, made available to the entire world at the same time, represents a radical shift in the astronomical knowledge base and will tremendously impact astronomy in the broadest sense of the term, for many, many years to come. Colleagues from all over the world are immersed in this ocean of positions, movements, brightness, colors, etc., confirming, reviewing and refining what we know and about to face, once again in history, the new.